Los simuladores virtuales como recurso didáctico para el aprendizaje de físico química con estudiantes de quinto semestre de la carrera de Pedagogía de las Ciencias Experimentales: Química y Biología, periodo noviembre 2020-abril 2021 - Villa Chafla, Sarai Patricia (2021)
Summary Education today is aimed at developing a transformative process with the help of TICS. The research problem is based on ¿How does the use of virtual simulators as a didactic resource contribute to Physical Chemistry learning? The objective was: "To propose using virtual simulators as a didactic resource for the learning of Physical Chemistry." The methodology was based on a non-experimental design. The type of research was field and bibliographic, designing a guide of experimental activities on the use of virtual simulators in Physics Chemistry that is considered a proposal for students and teachers of the fifth semester, whose level was descriptive. For data collection, the survey with its instrument, the questionnaire with ten strategic questions, and a population of 14 students of the fifth semester of the Pedagogy of Experimental Sciences: Biology and Chemistry, period November 2020 - April 2021, was used. The results confirmed that all students agree that it is essential to apply virtual simulators to link theory with practice. It was concluded that virtual simulators as didactic resources complemented the significant learning of Physical Chemistry being the most relevant: PhET, Crocodile Chemistry 605, Crocodile Physics, and Blogspot Virtual Laboratory because they allowed a feedback, deepening and generating relevant knowledge in students. Therefore, it is recommended to encourage using the proposed experimental activities guide as a useful tool for active learning in the subject.